Pedagogical Practices for Teaching Addiction Counseling Courses in CACREP‐Accredited Programs. Issue 1 (3rd April 2021) - Golubovic, Nedeljko; Dew, Brian; Rumsey, Amanda; Murphy, Thomas; Dispenza, Franco; Tabet, Saundra; Lebensohn‐Chialvo, Florencia
Abstract : We used a grounded theory approach to investigate educational strategies for teaching master's‐level addiction counseling courses. An emergent model of pedagogical practices, factors that influence development and implementation, and suggestions for counselor education programs are presented.